Nautical tourism : generator of Croatian economy development - Ivanić, Katarina (Array, 2018)
In nautical tourism, Croatia has great potential for further development; from the conditions of navigation, safety, destination content, traffic accessibility, natural beauty, traditional hospitality and gastronomic offer of island and coastal places, etc. Its features, at the same time, are the advantages of competing countries: purity of the sea and coastal places, beauty and preservation nature, climate, security, hospitality, country image and spatial layout of the marina. The disadvantages relate to insufficient availability and nautical ports equipment, insufficient education, low level of technical service at nautical ports. The research aimed at analysing the current state of nautical tourism in Croatia. The methods used, based on the collected data, have been analysed. The results of the analysis rely on the existing state of nautical tourism, which determines the importance of additional investment in this form of tourism. The aim of the research is to define and shape the necessary measures and development strategies to achieve the purpose of research: the development of nautical tourism contributes to the growth of Croatia’s economy.